2019
DOI: 10.1002/eap.1957
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and spatial structure of abiotic and biotic properties of lakes, wetlands, and streams at the national scale

Abstract: Broad‐scale studies have improved our ability to make predictions about how freshwater biotic and abiotic properties will respond to changes in climate and land use intensification. Further, fine‐scaled studies of lakes, wetlands, or streams have documented the important role of hydrologic connections for understanding many freshwater biotic and abiotic processes. However, lakes, wetlands, and streams are typically studied in isolation of one another at both fine and broad scales. Therefore, it is not known wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Nonetheless, the relative importance of climate in defining species habitat compared with the local environmental factors is somewhat poorly known in aquatic systems. Recently, King, Cheruvelil, and Pollard () showed that abiotic properties such as total phosphorus (TP) and total nitrogen (TN) values in U.S. lakes, streams, and wetlands were not dependent on water body categories; however, they demonstrated that percentage cover of aquatic vegetation was higher in lakes and wetlands, and lower in streams. Exploring factors that drive freshwater species distributions at various scales and in different ecosystems can improve our general understanding of species habitat preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the relative importance of climate in defining species habitat compared with the local environmental factors is somewhat poorly known in aquatic systems. Recently, King, Cheruvelil, and Pollard () showed that abiotic properties such as total phosphorus (TP) and total nitrogen (TN) values in U.S. lakes, streams, and wetlands were not dependent on water body categories; however, they demonstrated that percentage cover of aquatic vegetation was higher in lakes and wetlands, and lower in streams. Exploring factors that drive freshwater species distributions at various scales and in different ecosystems can improve our general understanding of species habitat preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Across landscapes, watersheds integrate catchment-scale variation in hydrology and geomorphology, as well as regional forcings including climate, biogeography, and anthropogenic disturbance, producing regionally coherent patterns in trophic structure, organic material and nutrient delivery, and productivity (Fergus et al 2011;King et al 2019). On the Pacific coast of Alaska and British Columbia, lakes within the same biogeographic regions often share similar water chemistry, hydrology and climate, resulting in broad, regionally defined patterns of lake productivity (Stockner and MacIsaac 1996).…”
mentioning
confidence: 99%
“…By moving beyond research focused on single, discrete waterbody types, we have also begun to find the remarkable 4 commonalities among seemingly disparate aquatic ecosystem types leading to more general theories for how waterbodies function. For instance, waterbodies across size and flow gradients have been shown to have similar controls on their nutrient limitation (Elser et al, 2007), metabolism (Yvon-Durocher et al, 2012), trophic cascades (Shurin et al, 2002), and responses to human activity (King et al, 2019).…”
mentioning
confidence: 99%
“…Numerous computing resources are putting advanced statistical tools at our finger tips for free. National, international, and global databases containing data from many thousands of waterbodies are inspiring new questions and becoming an increasingly important tool to understand aquatic ecosystems (King et al, 2019). And mobile technologies, social media, and open access philosophies are reshaping the ways limnologists communicate with each other and with the public.…”
mentioning
confidence: 99%
See 1 more Smart Citation